2005
DOI: 10.1212/01.wnl.0000156352.61328.cb
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of SUDEP

Abstract: This work lends support to the view that SUDEP is a seizure-related phenomenon and that control of tonic-clonic seizures is important in its prevention. Nocturnal supervision seems to protect against SUDEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
302
2
26

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(343 citation statements)
references
References 27 publications
13
302
2
26
Order By: Relevance
“…The National General Practice Study of Epilepsy (NG-PSE), a community-based study in the United Kingdom, saw the first case of SUDEP after 11,000 person-years of follow-up (Lhatoo and Sander 2001), and the results of the Medical Research Council Antiepileptic Drug Withdrawal Study showed that SUDEP is a rare event among patients with epilepsy in remission (1991). Information concerning risk factors for SUDEP is conflicting, but potential risk factors include: early adulthood, early onset of epilepsy (Nilsson et al 1999), long duration of epilepsy (Walczak et al 2001), uncontrolled seizures (mainly in those with TLE) (Walczak et al 2001, Sperling et al 1999, high seizure frequency (Walczak et al 2001, Langan et al 2005, certain seizure types (Walczak et al 2001, Kloster andEngelskjon 1999), higher numbers of AED (Nilsson et al 1999, Walczak et al 2001) and winter temperatures (Scorza et al 2007). Additionally, potential pathomechanisms for SUDEP are unknown, but it is very probable that cardiac arrhythmias during and between seizures, electrolyte disturbances, arrhythmogenic drugs or transmission of epileptic activity to the heart via the autonomic nervous system potentially play a role for SUDEP (Stollberger and Finsterer 2004).…”
Section: General Aspectsmentioning
confidence: 99%
“…The National General Practice Study of Epilepsy (NG-PSE), a community-based study in the United Kingdom, saw the first case of SUDEP after 11,000 person-years of follow-up (Lhatoo and Sander 2001), and the results of the Medical Research Council Antiepileptic Drug Withdrawal Study showed that SUDEP is a rare event among patients with epilepsy in remission (1991). Information concerning risk factors for SUDEP is conflicting, but potential risk factors include: early adulthood, early onset of epilepsy (Nilsson et al 1999), long duration of epilepsy (Walczak et al 2001), uncontrolled seizures (mainly in those with TLE) (Walczak et al 2001, Sperling et al 1999, high seizure frequency (Walczak et al 2001, Langan et al 2005, certain seizure types (Walczak et al 2001, Kloster andEngelskjon 1999), higher numbers of AED (Nilsson et al 1999, Walczak et al 2001) and winter temperatures (Scorza et al 2007). Additionally, potential pathomechanisms for SUDEP are unknown, but it is very probable that cardiac arrhythmias during and between seizures, electrolyte disturbances, arrhythmogenic drugs or transmission of epileptic activity to the heart via the autonomic nervous system potentially play a role for SUDEP (Stollberger and Finsterer 2004).…”
Section: General Aspectsmentioning
confidence: 99%
“…Seizure alarms and supervision at night are potential interventions to prevent seizure-related hypoxia by repositioning and inducing arousal [29]. Studies indicate that the vast majority of SUDEP cases are unwitnessed [13,14,17], suggesting supervision and early intervention may be helpful in prevention.…”
Section: Preventionmentioning
confidence: 99%
“…Due to the small samples with few included SUDEP cases in each study, it has been difficult to assess more than the strongest risk factors, and the precision of the risk estimates has been limited. To counteract these limitations, the ILAE Task Force on Epidemiology pooled data from four major case-control studies [19][20][21][22] of SUDEP that adopted similar SUDEP criteria and all used living epilepsy patients as controls. [23] This pooled analysis included altogether 289 SUDEP cases and 958 living epilepsy controls.…”
Section: Risk Factorsmentioning
confidence: 99%